A Multifactorial Comparison of Ternary Combinations of Essential Oils in Topical Preparations to Current Antibiotic Prescription Therapies for the Control of Acne Vulgaris‐Associated Bacteria. (26th January 2017) - Owen, Lucy; Grootveld, Martin; Arroo, Randolph; Ruiz‐Rodado, Victor; Price, Penny; Laird, Katie
Abstract : Acne vulgaris, a chronic condition associated with overgrowth of Propionibacterium acnes and Staphylococcus epidermidis, is commonly treated with antibiotics. However, the emergence of antibiotic resistance has resulted in a need for alternative therapies. The aim of this study is to develop a topical preparation incorporating essential oils (EOs) for use against acne‐associated bacteria and assess its efficacy against prescription therapies Dalacin T and Stiemycin. Antimicrobial screening of rosewood, clove bud and litsea EOs was conducted before interactions between binary and ternary combinations were determined against P .  acnes and S. epidermidis (type and clinical isolates) using minimum inhibitory concentrations and fractional inhibitory concentrations. The EOs were characterised by both gas chromatography–mass spectrometry and nuclear magnetic resonance. A combination of 0.53 mg/mL litsea, 0.11 mg/mL rosewood and 0.11 mg/mL clove bud was formulated into herbal distillates and compared with Dalacin T and Stiemycin against antibiotic sensitive and resistant isolates (erythromycin). The distillate with EO had synergistic activity against P. acnes (7log10 reduction) and indifferent activity against S. epidermidis (6log10 reduction); antimicrobial activity was either significantly ( p  ≤ 0.05) more antimicrobial or equivalent to that of Dalacin T and Stiemycin. This formulation may serve as a valuable alternative for the control of acne vulgaris‐associated bacteria. Copyright © 2017 John Wiley & Sons, Ltd.